Hog-eye - Meddaugh, Susan (Boston : Houghton Mifflin, 1995)
A young pig uses her ability to read to outwit a wolf that intends to eat her.
Keywords: Pigs -- Fiction; Wolves -- Fiction; Reading -- Fiction